Automatic depletion with Spectra Optia allows a safe 16% reduction of red blood cell pack consumption in exchanged sickle cell anemia patients. Issue 5 (12th February 2019) - Hequet, O.; Poutrel, S.; Connes, P.; Revesz, D.; Chelghoum, Y.; Kebaili, K.; Cannas, G.; Gauthier, A.; Guironnet‐Paquet, A.; Vocanson, M.; Nicolas, J.F.; Renoux, C.; et al.
Abstract : BACKGROUND: Chronic red blood cell exchanges (RBCXs) are frequently used to prevent complications in patients with sickle cell anemia, but the scarcity of matched red blood cell packs (RBCPs) is a serious concern. The main goal of this study was to compare the number of RBCPs used during RBCXs between the Spectra Optia (SO) device (with the automatic depletion step) and the former Cobe Spectra (CSP) device. STUDY DESIGN AND METHODS: The performances and safety of 300 SO sessions using the automatic depletion step (SO/DE) in 50 patients with sickle cell anemia under a chronic transfusion program over a 1‐year period were prospectively analyzed. The numbers of RBCPs saved using this protocol compared to the SO device without depletion and to the CSP device were determined. RESULTS: The SO/DE protocol appeared to be safe, as only 5% and 17% of the sessions were characterized by a significant decrease in blood pressure and increase in heart rate (grade 2 adverse events), respectively. Postapheresis hematocrit and fraction of cells remaining reached expected values. The SO/DE protocol required 16% fewer RBCPs compared to SO without depletion, allowing a mean saving of 12 RBCPs per patient and per year and 13% fewer compared to CSP device. Interestingly, the saving was more important for patients with high total blood volume and/or high preapheresis hematocrit. CONCLUSION: The SO/DE protocol is an efficient, safe and cost‐effective procedure for patients with sickle cell anemia under a chronic transfusion program.